Physics - "Abbott, A.F." (Heineman Educational Books: Oxford, 1989)
This is the latest edition that takes into account the requirements of the East African Examination Council. To reflect this, the 5th edition of Physics includes substantial new material on logic gates and their uses.
Keywords: Physics - Textbook